2012
DOI: 10.1002/app.38753
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and thermal degradation of poly(L‐lactide) in the presence of talc and modified talc

Abstract: Talc and talc modified with trimethoxy(octadecyl)silane (O-talc) were melt compounded with poly (L-lactide) (PLA). The crystallization behavior, tensile properties, and impact strength of the PLA composites were examined before and after the incorporation of talc and O-talc. The molecular weight of PLA in the PLA composites was measured as a function of the hydrolysis time and temperature. The effect of talc and O-talc on the thermal stability of PLA was examined and quantified by the activation energy of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The decrease in the film transparency as a consequence of the addition of inorganic filler has also been reported with other base polymers. Such an effect of an inorganic filler on the optical properties was explained as being not only due to the types of polymer matrix but also to the compatibility between the polymer matrix and the filler . Hong and Rhim reported that a polyethylene film without clay filler was more transparent than those with clay filler .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the film transparency as a consequence of the addition of inorganic filler has also been reported with other base polymers. Such an effect of an inorganic filler on the optical properties was explained as being not only due to the types of polymer matrix but also to the compatibility between the polymer matrix and the filler . Hong and Rhim reported that a polyethylene film without clay filler was more transparent than those with clay filler .…”
Section: Resultsmentioning
confidence: 99%
“…The use of natural talc is well known in literature. This filler has been used in the production of composites with different polymeric matrix, such as poly(vinyl alcohol), LLDPE/MWCNT, thermoplastic polyurethane, thermoplastic polyurethane/polypropylene blends, poly(L‐Lactide), polypropylene, poly(lactic acid), among others. Yousfi et al described the use of new synthetic talc as nanofillers reinforcement for polypropylene and polyamide 6 systems and polypropylene/polyamide 6 blends …”
Section: Introductionmentioning
confidence: 99%
“…A large number of researches have been carried out for talc particles pretreatment by using surface active agents such as silane coupling agents, stearate, isocyanate, and so on , which can be chemically grafted onto the talc surface. Nevertheless, the in situ grafting modification during the blending process is a facile and efficient method.…”
Section: Introductionmentioning
confidence: 99%